Applications of 3D PCA method for extraction of mean shape and geometrical features of biological objects set - Rychlik, Michal; Stankiewicz, Witold; Morzyński, Marek (Mathematical Modelling and Analysis, 2008)
This article presents application of the Principal Component Analysis method for analysis of geometry of biological objects and computation of three dimensional anthropometric database. In this work as the biological objects the fifteen human femur bones were used. The geometry of each bone was obtained by using 3D structural light scanner. For PCA analysis all objects have to be described with the same FEM mesh. To achieve this, the modified fluid registration was used. PCA decomposes the set of 3D objects into mean geometry and individual features (empirical modes) describing deviations from mean value. In this paper the mean shape and features of real bones were presented and discussed.First Published Online: 14 Oct 2010